PELATIHAN PENCEGAHAN KOROSI BESI DAN PEMELIHARAAN DENGAN MENGGUNAKAN OLI BEKAS - Prasetyawan, Dimas Tri; Paryati, Ninik (Universitas Islam 45 Bekasi, 2024)
A lack of public understanding regarding corrosion prevention has led to significant damage to iron-based objects due to corrosion. Therefore, preventive measures are necessary, including the utilization of used oil. Certain types of oil have been formulated with additives that can effectively prevent corrosion in metal components, particularly in machinery. This community service program aims to educate the public on how to prevent iron corrosion and conduct maintenance using readily available materials, especially used oil. When applied to iron surfaces, oil forms a protective layer that prevents oxidation and other forms of degradation. Lubrication with used oil has proven to be highly effective in corrosion prevention, as oil contains anti-corrosion properties that protect coated surfaces from rust. This community service activity was carried out in Karang Indah Village, Bojongmangu District, Bekasi Regency, with the objective of training the community to become more aware of the importance of maintaining cleanliness and preserving village infrastructure. The results of the training on iron corrosion prevention and maintenance using used oil demonstrated a positive impact, enhancing the community’s understanding of the dangers of corrosion and the importance of preventive measures to ensure the durability of iron-based objects. Through interactive socialization and training sessions, residents gained new insights into various corrosion protection methods, including the application of used oil, breadfruit leaf extract, anti-rust coatings, painting, and other maintenance techniques.